Religion, Self-Help, Science: Three Economies of Western/ized Buddhism - Payne, Richard K. (Journal of global buddhism, 2019)
Scholars of Buddhism in the United States have attempted to give order to the varieties of Buddhism that they encounter. Typically, such studies have focused on doctrinal, lineal, or socio-historical factors that are, in many ways, already familiar in the field of Buddhist studies. What has been less explored is the ways in which Buddhism has become institutionalized in the United States. This study explores how three pre-existing models of institutional organization have structured the forms that various Buddhisms have taken, regardless of their doctrinal, lineal or socio-historical background. Religion, self-help, and science comprise this three-fold structure. Understanding this three-fold structure involves adding a third term to the common opposition of religion as the transcendent sacred and science as the mundane secular. That third term is the immanent sacred, which is generally suppressed by semiotic pairing of the other two terms, but which is present in the culture of self-help. After discussing the historical background of the three-fold structure, the different economies of the three forms of institutionalization are considered, as well as two additional institutional forms and also hybrid forms.